Transcriptome Analysis of Leaf Senescence Regulation Under Alkaline Stress in Medicago truncatula - Dong, Shuwei; Pang, Wenhui; Liu, Zhe; Li, He; Zhang, Kangning; Cong, Lili; Yang, Guofeng; Wang, Zeng-Yu; Xie, Hongli (Frontiers in Plant Science, 2022)
In plants, the leaf is an essential photosynthetic organ, and is the primary harvest in forage crops such as alfalfa (Medicago sativa). Premature leaf senescence caused by environmental stress can result in significant yield loss and quality reduction. Therefore, the stay-green trait is important for improving the economic value of forage crops. Alkaline stress can severely damage leaf cells and, consequently, cause leaf senescence. To understand the molecular regulatory mechanisms and identify vital senescence-associated genes under alkaline stress, we used high-throughput sequencing to study transcriptional changes in Medicago truncatula, a model plant for forage crops. We identified 2,165 differentially expressed genes, 985 of which were identical to those in the dark-induced leaf senescence group. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses showed that the 985 genes were mainly enriched in nutrient cycling processes such as cellular amino acid metabolic processes and organic substance catabolic processes, indicating nutrient redistribution. The other 1,180 differentially expressed genes were significantly enriched in the oxidoreductase complex, aerobic respiration, and ion transport. Our analysis showed the two gene sets guiding the coupled physiological and biochemical alterations play different roles under alkaline stress with a coordinated and integrated way. Many transcription factor families were identified from these differentially expressed genes, including MYB, WRKY, bHLH, and NAC which have particular preference involved in stress resistance and regulation of senescence. Our results contribute to the exploration of the molecular regulatory mechanisms of leaf senescence in M. truncatula under alkaline stress and provide new candidate genes for future breeding to improve the biomass and quality of forage crops.